2014
DOI: 10.4236/jbise.2014.76040
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality of People with Spinal Cord Injury: Knowledge, Difficulties and Adaptation

Abstract: Expressing sexuality is an important part of life, whether the person has a spinal cord injury (SCI) or not. This study investigated the sexual activity before and after SCI, the difficulties, and adjustments made by these people in relation to their sexuality. This is a qualitative study conducted with 14 people with SCI through semi-structured interviews, which we analyzed in light of pertinent literature and organized into three themes: sexual activity before and after SCI; difficulties in performing sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…The physical changes caused by this condition impact on the life of people who have the trauma directly, including the aspect of sexual satisfaction, thus interfering with the psychological and social components as a consequence of an altered self-perception. (1,2) The worldwide incidence of spinal cord trauma is from 15 to 40 new cases per year per one million people. In Brazil, the estimated incidence is 40 new cases per year per one million people, with 80% of the victims being men and 60% between 10 and 30 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical changes caused by this condition impact on the life of people who have the trauma directly, including the aspect of sexual satisfaction, thus interfering with the psychological and social components as a consequence of an altered self-perception. (1,2) The worldwide incidence of spinal cord trauma is from 15 to 40 new cases per year per one million people. In Brazil, the estimated incidence is 40 new cases per year per one million people, with 80% of the victims being men and 60% between 10 and 30 years old.…”
Section: Introductionmentioning
confidence: 99%
“…(8) To achieve this goal, it is essential that people with spinal cord injury receive guidance on possible changes and adaptation methods, because information may effectively contribute to clarifying doubts and reducing fears regarding the new health condition. (1) There is a lack of educational materials oriented to the sexuality of people with spinal cord injury. It has been observed that studies focused on sex education have been overlooked by those centered at the care to the patients, treatment for the injury, and adaptations to the changes in the acute phase which follows the trauma.…”
Section: Introductionmentioning
confidence: 99%
“…In another study discovered that compared their sexual experiences from pre-and post-SCI and described that their sexual ability was decreased as well as quality of sexual life was also decreased [12]. Other study comparing the sexuality of women with SCI before and after injury it was found a significant lowering in sexual desire, impaired lubrication and worsened ability of sexual activity [14].…”
Section: Quality Of Sexual Life (Before and After Injury)mentioning
confidence: 99%
“…In contrast another study revealed that sexual function and SCI shows that sexual pleasure are possible for women having spinal cord injury [9]. Sexuality is expressed in different ways, namely by desires, feelings, thoughts, emotions, attitudes, and behaviors, influenced by cultural context and historical moments [12].…”
Section: Happiness Of Sexual Lifementioning
confidence: 99%
“…One of these sexual rights is tied to the basic human right to attain education and information [7,8]. Since learning how to cope with the long-term consequences of an SCI usually starts during inpatient rehabilitation, nurses could play an important role in fulfilling this right by providing patient education and information due to the intimate contact they have with their patients [9,10].…”
Section: Introductionmentioning
confidence: 99%